Analysis of the Effect of Private Healthcare Financing on Poverty in Nigeria: Evidence from Edo State - O, Olaniyi; Idris, Abubakar (Asian Journal of Economics and Empirical Research, 2021)
Poverty is one of the problems that challenge economies in Africa. Though it is a complex phenomenon which requires efforts by different experts to reduce or eliminate, conventional wisdom posits that “health is wealth”. Health status is a component of human capital development which plays a fundamental role in the poverty and well-being of individuals and national economies. Paradoxically the cost of accessing quality healthcare is an important contributor to income poverty among low income households. Thus adequate healthcare financing mechanisms (public and private) are required to attain quality health outcomes. This study therefore investigates the adequacy or otherwise of the current means of private health care financing in Edo state of Nigeria and it employed the survey method and multinomial logistic regression technique. Results revealed that the dominant means of private health care financing in Edo state is “out of pocket” payments which has negative effect on the income of households. It therefore recommends the introduction of a more effective collective healthcare financing mechanism to mitigate the financial burden associated with out-of-pocket spending. Also funding should be provided for research and development of locally manufactured drugs with high local content to enhance the availability and affordability of effective drugs.